The Effect of Lithium Excess on NMC-721 using Oxalate Co-precipitation - Revina Dea Nanda; Sigit Aryo Kristianto; Evvy Kartini; Muhammad Fakhrudin (NBRI Press, 2023)
Lithium Nickel Manganese Cobalt Oxide (Li-NMC) has been regarded as preferred cathode material for Lithium-ion battery (LIB), compared to other materials such as Lithium Cobalt Oxide (LCO) and Lithium Manganese Oxide (LMO). Ni-rich content displays severe cycling performance and needs to be addressed to improve its performance of electric vehicle. This research focused on synthesis NMC-721 precursors with the oxalate co-precipitation. Furthermore, a variation of lithium hydroxide with the excess of 3% and 5% were added into the precursors, then calcined at temperature 800 ℃ for 12 hours. The product of precursor was analyzed by X-Ray Fluorescence (XRF) and Particle Size Analysis (PSA) to analyze elemental composition and particle size, respectively. Meanwhile, the NMC-721 cathodes were characterized by an X-Ray Diffraction. The XRF data of precursor shows the ratio of transition metals at 7.5:1.5:1 identifying that more Ni content and less Mn content in the NMC-721, due to oxalate co-precipitation. The PSA shows that the average diameter of the precursor was 9.19 ± 0.31 (µm). The XRD result shows that the crystal structure of NMC-721 cathode belongs to hexagonal structure. It can be concluded that the NMC-721 were successfully synthesized and can be applied for lithium-ion battery.